Reworking ‘defective knowledge goods’ in the knowledge production ‘factory’ through the peer-review process (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
Manufacturing defects are errors in product design or production that can cause harm, injury, or fatality to consumers. These defects are relevant to knowledge production in academic manuscript writing. This article examines how peer-review comments assist academic knowledge manufacturers in reworking their products to meet journal production requirements. The study involved 30 anonymized research articles from four Zimbabwean universities, which were returned to authors by prospective journals with feedback to revise and resubmit. The articles were written in English by authors who spoke English as their first language or as their second, third, or fourth language. The articles were reviewed using Microsoft Word's track changes function, along with reviewers' reports and editors' comments. The study found that while authors sometimes find reviewers' comments offending, they help enhance the quality of a research manuscript by improving its language, readability, and logical structure, especially when authors write in their second, third, or fourth language.
Keywords: peer-review; peer-review comments; knowledge production; Zimbabwe